Indonesia Economic Quarterly, June 2019 : Oceans of Opportunity - World Bank (World Bank, Washington, DC, 2019)
In 2018, Indonesia’s coordinated and prudent macroeconomic policy framework underpinned steadyeconomic growth, amid global volatility and several natural disasters. Real GDP growth strengthened to 5.2 percent yoy in 2018 from 5.1 percent in 2017. Growth decelerated only slightly in Q1 2019, to 5.1 percent yoy. Quarterly GDP growth has been broadly stable, remaining within a narrow range of 4.9-5.3 percent yoy for 14 consecutive quarters. The drivers of growth shifted in Q4 2018 and Q1 2019, as investment growth decelerated from multi-year highs, and both private and government consumption picked up. Investment slowed because of inventory destocking and easing fixed investment growth due to delays in new public projects in response to current account concerns, political uncertainty ahead of the general elections, and deteriorating prices of thecountry’s key commodity exports and a maturing investment cycle in the mining sector. On the other hand, growth of private and government consumption gained on stronger spending by political parties and civil servant bonuses. Private consumption was also supported by low inflation and abuoyant labor market. Indonesia’s oceans can be leveraged to make a larger contribution to the economy, both through higher revenues from tourism and fisheries and by enhancing resilience to natural disasters and climate change. This edition therefore discusses the importance of the maritime economy to Indonesia’s economic development and presents the challenges and opportunities the country faces in leveraging the maritime economy for greater prosperity.